Suspension, Restoration and Extension of Procedural Terms in Civil Proceedings - Yesayan, Vardush (Bulletin of Yerevan University C: Jurisprudence, 2022)
In the current article, the author discusses and analyzes the concept of suspension, restoration and extension of procedural terms in civil proceedings. The peculiarities and features of suspension of the procedural terms are also discussed in the article. The legal possibility and features of restoring the missed procedural terms (deadlines) were studied and discussed. The article discusses that after the end of the procedural 68 terms, persons participating in the case are deprived of certain procedural rights except when the court satisfies the motion on restoring the missed procedural term. The article discusses the extension of procedural terms which is different from the concept of restoration. The concept and features of extension of the procedural terms were analyzed in the article. It is argued that the reasons for missing the procedural deadlines should be assessed based on legal criteria, excluding any arbitrart and unreasonable approach. Such power should be exercised in accordance with the law, on a basis equally understandable for all persons.
Keywords: time limit; procedural action; mediation; restoration of procedural terms; extension of procedural terms; suspension of procedural terms